The Relations between Student Foreign Language Anxiety and Social Variables - Farkas, János; Lázár, Tímea; Valnerné Török, Eszter; Amin, Mohammad Bin; Hajdu, Zita (Central European Journal of Educational Research, 2025)
Due to the labour market expectations, universities are responsible for preparing their students for competitive employment in Hungary or abroad. However, language anxiety is an insurmountable problem for many people, making it difficult to learn foreign languages, even though a confident command of them is a key factor in any job interview and essential in the world of work. This complex is one of the main factors hindering language learning, affecting all people to either a greater or lesser extent. In 2023, the University of Debrecen’s researchers studied the impact of language anxiety on foreign language learning, surveying approximately 400 students of the university’s commerce, marketing, and business management courses. After having a questionnaire filled in, descriptive statistical and cross-tabulation analyses were conducted, and the focus was on analysing the impact of social variables on language anxiety. Our research shows that women are significantly more anxious than men. Students who work while studying and use their foreign language skills at work experience significantly more anxiety than students who do not use a foreign language. Parents’ language skills significantly affect their children’s language anxiety. The research topic is relevant, as it highlights the importance of teaching strategies to reduce language anxiety in university foreign language teaching. The present study facilitates the teaching of those students who would not be able to overcome the anxiety barrier.